1.已知数列{an},{bn}满足a1=2,a2=4,bn=a(n+1)-an,b(n+1)=2bn+2.

1个回答

  • 1.(1)∵b(n+1)=2bn+2

    ∴b(n+1)+2=2bn+4

    ∴[b(n+1)+2]/(bn+2)=(2bn+4)/bn+2=2

    ∴数列{bn+2}是公比为2的等比数列

    (2)由第一题可知bn+2=2*2^(n-1)

    =2^n

    ∴bn=2^n-2

    所以2^n-2=a(n+1)-an

    a1=2

    a2-a1=2

    a3-a2=2^2

    a4-a3=2^3

    …………

    an-a(n-1)=2^(n-1)

    以上式子相加

    得:an=2+2+2^2+2^3+……+2^(n-1)

    =2+{2*[1-2^(n-1)]/(1-2)}

    =2^n

    2.(1)∵a1=2,a1+a2+a3=12

    ∴a1+a1+d+a1+2d=12

    ∴d=2

    ∴an=2+2(n-1)

    2n

    (2)sn=2*x+4*x^2+6*x^3+8*x^4+……2n*x^n

    x*sn= 2*x^2+4*x^3+6*x^4+……(2n-2)*x^n+2n*x^(n+1)

    两式相减

    得(1-x)*sn=2x+2x^2+2x^3+2x^4+……2x^n-2n*x^(n+1)

    ={[2x(1-x^n)]/1-x}-2n*x^(n+1)

    所以sn=……

    你会算的吧